Beclin 1 is dispensable for chromosome congression and proper outer kinetochore assembly. (21st August 2015) - Fava, Luca L; Rainer, Johannes; Haschka, Manuel D; Geley, Stephan; Villunger, Andreas
<x xml:space="preserve">Abstract</x> This is a correspondence about "Beclin‐1 is required for chromosome congression and proper outer kinetochore assembly". <boxed-text content-type="graphic" id="embr201540731-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>